Mega Monopoly Game for Disaster Mitigation Learning in the Context of Independent Learning for Children Aged 5-6 Years - Ainul Nur Khusna; Imron Arifin; Pramono (Universitas Pendidikan Ganesha, 2023)
Disaster events cause various impacts on victims, especially children. Problems in the field show that many PAUD institutions still need a game related to disaster mitigation. It is essential to carry out disaster mitigation education in PAUD units to form attitudes in early childhood. This research aims to analyze how the development of the mega monopoly game can improve the ability to save themselves from 5 types of disasters in children aged 5-6 years. This research is classified as a development research developed using the ADDIE model. The subjects involved in this research were 2 experts and 48 children. Data was collected using observation, interviews, and questionnaires, with research instruments in the form of media validity sheets. The data obtained in the research was then analyzed using quantitative analysis techniques. The research analysis results show that the validation results of PAUD material and game experts obtained an average of 92.20% and 90%. The recapitulation results of small group trials were 96.87%, and large group trials were 98%. Based on these results, the mega monopoly game for learning disaster mitigation for children aged 5-6 years is considered very valid and suitable. This research implies that the developed mega monopoly game can be used by teachers in learning to improve the ability to save themselves when a disaster occurs in children aged 5-6 years.